Anisotropic-Material-Induced Rotation of Field Distribution in Circular Plasmonic Resonator - Xiaokang Song; Shilei Li; Yuanyuan Chen; Yinxing Ding; Gaoyan Duan; Lulu Wang; Li Yu (IEEE Photonics Journal, 2019)
A metal–insulator–metal plasmonic structure that contains a circular cavity with anisotropic material (AM) is designed and numerically simulated. Attributed to filling the cavity with AM, the standing wave patterns in the cavity rotate clockwise as the wavelength increases, resulting in a new valley on the transmission spectrum, which will not appear in the isotropic-material case. In order to understand the underlying physical mechanism of the phenomena, the influences of the parameters of AM, such as optical axis angle and refractive indexes, on transmission spectrum were investigated. All results can be explained well by the index ellipsoid method and the coupled mode theory. This work shows the unique role of AM in the plasmonics nanostructure and these phenomena may have potential applications in the nanoscale integrated photonic circuits.